Parent Education as Effort to Improve Sleep Quality Handling in ASD Children at Sekolah Luar Biasa Cimahi City (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Autism Spectrum Disorder (ASD) is a condition that affects the development of a child's brain, leading to issues in verbal and nonverbal communication. Children with ASD often exhibit distinctive symptoms related to sleep problems. The cause of these sleep issues in children with ASD is linked to differences in the heritability of melatonin biosynthesis, which is lower compared to serotonin, with a prevalence rate of about 50-80%. The impact of sleep problems in children includes cognitive and behavioral disorders such as increased activity, inability to control emotions, learning difficulties, aggression, and more. These conditions pose challenges for parents and teachers at school, necessitating educational activities for both parents and teachers to improve sleep quality management in children with ASD. This activity aims to provide parents with understanding and insight into identifying sleep problems and efforts to enhance the quality of sleep in children with ASD. The method employed involves educational activities in the form of lectures and discussions with parents of students with ASD at special schools in the Cimahi City area. This activity uses an analytical observational method with a cross-sectional study approach. The results show that parents from 5 SLBs participated in the education, with N=126 parents attending. Among them, 52 children with ASD were identified, and 36 of these 52 children had sleep problems. Most parents practiced sleep hygiene, and a few used pharmacological methods to improve sleep quality.